Precision and reliability for measurement of change in MRI lesion volume in multiple sclerosis: a comparison of two computer assisted techniques. Issue 1 (1st July 1998) - Molyneux, P D; Tofts, P S; Fletcher, A; Gunn, B; Robinson, P; Gallagher, H; Moseley, I F; Barker, G J; Miller, D H
Abstract : OBJECTIVE: The serial quantification of MRI lesion load in multiple sclerosis provides an effective tool for monitoring disease progression and this has led to its increasing use as an outcome measure in treatment trials. Segmentation techniques must display a high degree of precision and reliability if they are to be responsive to small changes over time. This study has evaluated the performance of two such techniques, the manual outlining and contour methods, in serial lesion load quantification. METHODS: Sixteen patients with clinically definite multiple sclerosis were scanned at baseline and after two years. Scan analysis was performed twice, independently by three observers using each technique. RESULTS: For the absolute lesion volumes the median intrarater coefficient of variation (CV) was 3.2% for the contour technique and 7.6% for the manual outlining method (p<0.005), the interrater CVs were 3.8% and 6.1% respectively (p<0.01) and the reliability of both techniques was very high. For the change in lesion volume the intrarater and interrater repeatability coefficients were respectively 2.6 cm 3 and 2.8 cm 3 for the contour technique, and 3.3 cm 3 and 3.7 cm 3 for the manual outlining method (lower values reflect higher precision). The values for intrarater and interrater reliability for measuring change in lesion volume were respectively, 0.945 and 0.944 for the contour technique, and 0.939 and 0.921 for the manual outline method (perfect reliability = 1.0). CONCLUSIONS: With such high values for reliability, the impact of measurement error in lesion segmentation on sample size requirements in multiple sclerosis treatment trials is minor. This study shows that a change in lesion volume can be measured with a higher level of precision and reliability with the contour technique and this supports its further application in serial studies.